2023
DOI: 10.3390/molecules28145534
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Polymer-Reinforced Mechanical Properties of SiO2 Aerogels: A Review

Abstract: Silica aerogels are considered as the distinguished materials of the future due to their extremely low thermal conductivity, low density, and high surface area. They are widely used in construction engineering, aeronautical domains, environmental protection, heat storage, etc. However, their fragile mechanical properties are the bottleneck restricting the engineering application of silica aerogels. This review briefly introduces the synthesis of silica aerogels, including the processes of sol–gel chemistry, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 156 publications
0
5
0
Order By: Relevance
“…During the study, it was found that the technology for adding aerogel to the admix should be modified. The causes of technology modification are mentioned in the literature review [17]. In the second series of samples, the aerogel was first mixed with isopropyl alcohol and then added to the dry concrete mix.…”
Section: Concrete MIX Proportionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study, it was found that the technology for adding aerogel to the admix should be modified. The causes of technology modification are mentioned in the literature review [17]. In the second series of samples, the aerogel was first mixed with isopropyl alcohol and then added to the dry concrete mix.…”
Section: Concrete MIX Proportionmentioning
confidence: 99%
“…Hence, solvents (most often alcohols) are used to ensure the homogeneity of the mixture. These reactions are usually performed with ethanol or methanol [17]. Therefore, it is necessary to change the water-cement ratio [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The physio-chemical parameters of different polymers play a very significant role in defining the properties of the subsequent aerogel. Some important properties of polymers include the surface area of the polymer [76,77], chemical structure [78], porosity, density, polymer solubility, thermal stability [79], and the hydrophilic or hydrophobic nature of any specific polymer. Generally, for synthesising aerogels, biopolymers are mainly considered to be utilised in biomedical applications.…”
Section: Important Properties Of Polymers Used For Biomedical Applica...mentioning
confidence: 99%
“…1−4 Silica aerogels have been considered first-choice functional soft materials due to their high thermal resistance, low bulk density, and industrial production capability, and are widely used for safety and energy applications. 5 However, their intrinsically poor mechanical properties have led to various modifications from different preparation methods using chemical precursors to manipulation of parameters and reinforcement with different materials, including polymers, to improve mechanical strength through porosity and a beadlike network structure. Despite these advancements, the use of Pickering emulsionbased methods for the preparation of silica aerogels is still unexplored, which represents a significant gap in aerogel technology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Aerogels are known for their densely packed, lightweight porous solid structures with low thermal conductivity. Silica aerogels have been considered first-choice functional soft materials due to their high thermal resistance, low bulk density, and industrial production capability, and are widely used for safety and energy applications . However, their intrinsically poor mechanical properties have led to various modifications from different preparation methods using chemical precursors to manipulation of parameters and reinforcement with different materials, including polymers, to improve mechanical strength through porosity and a beadlike network structure.…”
Section: Introductionmentioning
confidence: 99%